When REDD+ goes national: a review of realities, opportunities and challenges - Peskett, L.; Brockhaus, Maria (Center for International Forestry Research, 2009)
The development of national REDD+ strategies has progressed. Common challenges include establishing appropriate national institutions that link into ongoing processes; ensuring high level government commitment; achieving strong coordination within governments and between state and non-state actors; designing mechanisms to ensure participation and benefit sharing; and establishing monitoring, reporting and verification (MRV) systems. The different agendas of actors involved in policy formulation at the national level reflect those at the international level. Conflicting interests could make it difficult to overcome the key challenges and hamper coordination, which could reduce efficiency in formulating and implementing REDD+ actions. Issues such as participation, land tenure and other reforms are key issues in developing effective REDD+. But it is unclear to what extent these are mere rhetoric or whether they represent genuine motivation to address such issues the context of REDD+.